Investigation of a Micro-test for Circulatory Autonomic Nervous System Responses - Moser, Maximilian; Frühwirth, Matthias; Messerschmidt, Dietmar; Goswami, Nandu; Dorfer, Leopold; Bahr, Frank; Opitz, Gerhard (Frontiers in Physiology, 2017)
Aims and Objectives: The autonomic nervous system plays an important role in homeostasis and organismic recreation, control of immune function, inflammation, and bone growth. It also regulates blood pressure and orthostasis via vagal and sympathetic pathways. Besides recording of heart rate variability, which characterizes medium (1-5 min) and long term (circadian) autonomic tone or modulation, no gentle tests of short-term autonomic reactivity and control are available. In 1976 Nogier described a short time cardiovascular reaction (“Réflexe Auriculo Cardiaque”, RAC) which could be used to investigate short term autonomic reactions without changing system characteristics and thus being repeatable in short intervals. In this paper we investigated the possible application of the Nogier reaction as a micro-test for the identification of a disturbed sensitivity or reactivity of the autonomic nervous system. Methods: We statistically analyzed cardiovascular signals derived during the application of small repeated stimuli utilizing methods of signal averaging to characterize the physiological background. Specifically, the Nogier reaction was investigated using simultaneous recordings of ECG, pulse waves, and respiration. Results: Significant fast (delay 1-5 sec) and slower (delay 6-12 sec) cardio-autonomic responses to different stimuli which characterize short term were observed. From time characteristics and type of signals where they occur we deduce that fast changes observed in heart rate are vagal reactions to the small stimuli whereas slower changes observed in pulse waves stem from sympathetic nervous system responses. Conclusions: The investigated autonomic microtest opens the possibility to differentially investigate both limbs of the autonomic nervous system with minimal stimuli. It can be performed within seconds and does not change the set point of the system in opposition to less subtle tests such as Valsalva maneuver. Therefore it is well-suited for quick, repeated measurements of autonomic nervous system reactivity.